2009
DOI: 10.1002/jcc.21460
|View full text |Cite
|
Sign up to set email alerts
|

Accurate conformation‐dependent molecular electrostatic potentials for high‐throughput in silico drug discovery

Abstract: The atom-centered partial charges-approximation is commonly used in current molecular modeling tools as a computationally inexpensive alternative to quantum mechanics for modeling electrostatics. Even today, the use of partial charges remains useful despite significant advances in improving the efficiency of ab initio methods. Here, we report on new parameters for the EEM and SFKEEM electronegativity equalization-based methods for rapidly determining partial charges that will accurately model the electrostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 54 publications
0
66
0
Order By: Relevance
“…Over the past 27 years, EEM strongly influenced related areas, such as in-silico screening [6], chemical reactivity descriptors [7,8,9] and empirical models for molecular potential energy surfaces, hereafter referred to as (polarizable and possibly reactive) force fields [10,11,12,13,14,15,16]. Extensive calibration studies have demonstrated the accuracy of atomic charges and the parameter transferability of EEM [17,18,19,20,21,22,14,23] and its recent generalizations, the Split-Charge Equilibration (SQE) [15,24,25,26] and Atom-Condensed Kohn-Sham approximated to Second order (ACKS2) [16].…”
Section: One Of Its Modern Incarnations Is the Electronegativity Equamentioning
confidence: 99%
“…Over the past 27 years, EEM strongly influenced related areas, such as in-silico screening [6], chemical reactivity descriptors [7,8,9] and empirical models for molecular potential energy surfaces, hereafter referred to as (polarizable and possibly reactive) force fields [10,11,12,13,14,15,16]. Extensive calibration studies have demonstrated the accuracy of atomic charges and the parameter transferability of EEM [17,18,19,20,21,22,14,23] and its recent generalizations, the Split-Charge Equilibration (SQE) [15,24,25,26] and Atom-Condensed Kohn-Sham approximated to Second order (ACKS2) [16].…”
Section: One Of Its Modern Incarnations Is the Electronegativity Equamentioning
confidence: 99%
“…After the introduction of EEM in the seminal paper of Mortier, 4 the model was extensively validated and applied to diverse chemical systems, including inorganic solids, 5-12 organic molecules, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] biomolecular systems [30][31][32][33] and metal-organic frameworks. 34 These successes are the basis for the wide-spread adoption of EEM as a polarizable force field (PFF) used in high-throughput in-silico screening 35 and in molecular mechanics force fields. 9,13,15,20,21,[24][25][26]31,[36][37][38] Besides its practical utility, EEM is also of fundamental importance because it explains the molecular charge distribution with just a few simple equations and a set of transferable parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 262 published compounds with known activities and unknown binding modes [15][16][17][18][19][45][46][47][48] (Supplementary Material Table SM-1) were collected. As an extension of previously reported applications [39,42,[45][46][47], in order to evaluate the 3-D QSAR model predictive abilities, either ligand-based (LB) or SB molecular alignments were ruled out by means of the programs Surflex-Sim [48], Omega/Rocs [49][50][51][52] and Balloon/ShaEP [53][54][55] for the LB and AutoDock4 [56], AutoDock Vina (herein just Vina), DOCK, Plants, ParaDocks and Surflex-Dock for the SB. Only the LB and SB best performing programs were then used to align the external test set compounds (see Test Set Selection section) and assess the 3-D QSAR models by means of pIC 50 predicted values (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To rule out LB molecular alignment 3 different LB programs (free for academia) were used: (1) Surflex-Sim [48]: an automatic flexible program which uses the principle of morphological similarity; (2) Omega/Rocs [49][50][51][52]: which generates (Omega) a multi-conformer database and performs a rigid shape-based superposition and scoring of molecules (Rocs), and (3) Balloon/ShaEP [53][54][55]: which, similarly to the previous, generates conformers (Balloon) and performs rigid-body superimposition (ShaEP). The LB alignment procedure assessment was conducted at different levels of difficulties:…”
Section: Lb Alignment Assessmentmentioning
confidence: 99%